Memórias femininas no Bom Pastor- PE: gênero, repressão e resistência durante a Ditadura Civil-Militar brasileira (1964-1985) - Silva, Tatianne Ellen Cavalcante (2017)
The present research emerges from nowadays needs to inquire about Brazilian historic time in between 1964-1985, temporality where the country lived under a civil-military dictatorship. Thinking about this period and the acting subjects in combat against the system of oppression and repression configures here as resistance. Thus, we will try to understand this period starting by the memories of the women inserted in the political struggles, acted in the confrontation with the antidemocratic forces. That said, we aimed to analyze the memories of women militants who were political prisoners in the Bom Pastor Penal Colony between 1969 and 1979 in the city of Recife and the resistance they practiced during the militancy that began in 1964, year of the coup d‘etat and ending in 1985. To this it is necessary to understand the cartographic traces and experiences of the twenty-four (24) militant women from the discourses contained in the reports of memory and in the individual records relating to the period of their detention. To discuss the forms of resistance exercised by left-wing militants against the civil-military dictatorship and their closure in prison. In addition to problematizing the construction of women's memories from the testimonial speeches contained in the documentary Vou contar para meus filhos. To do so, we use the contributions of the field of Cultural History, choosing to produce a history that focuses on the participation of women, in this way we seek to discuss categories such as gender and memory, which helped us to make new looks about the period covered, showing these subjects still shaded to the pages of historiography.